Immune response to COVID‐19 vaccination is attenuated by poor disease control and antimyeloma therapy with vaccine driven divergent T‐cell response. (17th February 2022) - Ramasamy, Karthik; Sadler, Ross; Jeans, Sally; Weeden, Paul; Varghese, Sherin; Turner, Alison; Larham, Jemma; Gray, Nathanael; Carty, Oluremi; Barrett, Joe; Bowcock, Stella; Oppermann, Udo; et al.
Summary: Myeloma patients frequently respond poorly to bacterial and viral vaccination. A few studies have reported poor humoral immune responses in myeloma patients to COVID‐19 vaccination. Using a prospective study of myeloma patients in the UK Rudy study cohort, we assessed humoral and interferon gamma release assay (IGRA) cellular immune responses to COVID‐19 vaccination post second COVID‐19 vaccine administration. We report data from 214 adults with myeloma ( n  = 204) or smouldering myeloma ( n  = 10) who provided blood samples at least three weeks after second vaccine dose. Positive Anti‐spike antibody levels (> 50 iu/ml) were detected in 189/203 (92.7%), positive IGRA responses were seen in 97/158 (61.4%) myeloma patients. Only 10/158 (6.3%) patients were identified to have both a negative IGRA and negative anti‐spike protein antibody response. In all, 95/158 (60.1%) patients produced positive results for both anti‐spike protein serology and IGRA. After adjusting for disease severity and myeloma therapy, poor humoral immune response was predicted by male gender. Predictors of poor IGRA included anti‐CD38/anti‐BCMA (B‐cell maturation antigen) therapy and Pfizer‐BioNTech vaccination. Further work is required to understand the clinical significance of divergent cellular response to vaccination.